Oxidative Stress as an Important Factor in the Pathophysiology of alzheimer's Disease (Revista Brasileira Multidisciplinar, 2013)
Oxidative stress has been associated to play a crucial role in the pathogenesis of many diseases, including neurodegenerative diseases. Alzheimer's disease is an age-related neurodegenerative disorder, which is recognized as the most common form of dementia. In this article, the aim was to review the involvement of oxidative stress on Alzheimer's disease. Alzheimer's disease is histopathologically characterized by the presence of extracellular amyloid plaques, intracellular neurofibrillary tangles, the presence of oligomers of amyloid-? peptide and loss of synapses. Moreover, the brain and the nervous system are more prone to oxidative stress and oxidative damage influences the neurodegenerative diseases. However, increased oxidative damage, mitochondrial dysfunction, accumulation of oxidized aggregated proteins, inflammation, and defects in proteins constitute complex intertwined pathologies that lead to neuronal cell death. Mitochondrial mutations on deoxyribonucleic acid and oxidative stress contribute to aging, affecting different cell signaling systems, as well as the connectivity and neuronal cell death may lead to the largest risk factor for neurodegenerative diseases such as Alzheimer's Disease.
Keywords: Oxidative stress; Alzheimer's Disease; Neurodegenerative diseases.